Pengaruh Capital Intensity Dan Leverage Terhadap Tax Avoidance Pada Perusahaan Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun 2019-2021 - Evelyn Tio Rizki Hutabarat; Anik Yuliati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine and analyze the effect of capital intensity, profitability, and leverage on tax avoidance in companies listed on the Indonesia Stock Exchange in the property and real estate sector during 2019-2021. The research method used is quantitative and uses research variables including "Capital Intensity" (X1), "Leverage" (X2), and "Tax Avoidance" (Y). The sample of companies using purposive sampling method in this study obtained 22 property and real estate companies during the 2019-2021 period. The research data used is secondary data with a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). This study has results that show, a) p-value capital intensity on tax avoidance 0.014 < 0.05; c) p-value leverage on tax avoidance 0.003 > 0.05. Conclusion, capital intensity and leverage can significantly affect the increase in tax avoidance in property and real estate sector companies. Keywords: Tax Avoidance, Capital Intensity, Leverage, Property and Real Estate